Paradox as a Logic Problem - Durhan, Gülümser (Erciyes Üniversitesi, 2019)
The paradox is, at first glance, the right of an expression or reasoning activity to create a contradiction, drag it into a dead end and become inexhaustible. A paradoxical expression or reasoning cannot solve this dilemma in itself, without a reference to i ts own or without the need for additional precursors. For this reason, paradoxical propositions do not represent a situation that can be expressed as 'true or false', but a logical contradiction that can be determined as 'both true and false', can not be decided and unresolved situations. Therefore, the paradoxicality of such a proposition or reasoning cannot be solved by the choice of one of the dilemmas. Such that, when the paradoxical expression is accepted as true, it is false, also, it is true that when is accepted as false and cannot reach a logical, explicit and definite conclusion because the answer is different in view of different perspectives. For that reason, the paradox appears as an unresolved problem and conflict. That is the realization of this nonsolution, in fact, corresponds to the starting point of thinking. Because being in search for a solution rather than attaining solution, developing different perspectives, being on the road rather than being at the end of it as a philosophical aim is precisely the basic practice of the paradox  and in this way the paradox is a mental dynamic. For this reason, the aim of our study is to emphasize what the paradox is in its contribution to philosophical thought and how it leads to a stalemate as problem of logic.

Paradoks, ilk bakista dogru olan bir ifade veya akil yürütme etkinliginin bir çeliski olusturmasi, çikmaza sürüklemesi ve durumun içinden çikilamaz bir hal almasidir. Paradoksal bir ifade ya da akil yürütme kendi içindeki bu çikmazini, kendi disinda bir açiklamaya yönelmeden ya da ek öncüle ihtiyaç duymadan çözememektedir. Bu nedenle paradoksal önermeler, 'ya dogru ya yanlis' olarak ifade edilebilecek bir durumu degil, 'ne dogru ne de yanlis' olarak belirlenebilecek mantiksal çeliskiyi, karar verilemez hali ve çözümsüz durumlari göstermektedir. Dolayisiyla böylesi bir önermenin ya da akil yürütmenin paradoksalligi, çikmazlardan birinin seçimiyle de çözülememektedir. Öyle ki paradoksal ifade; dogru kabul edildigi zaman yanlis, yanlis kabul edildigi zaman da dogru olmakta ve bu nedenle paradokslarda mantiksal manada zorunlu, açik seçik ve kesin bir sonuca ulasilamamaktadir. Zira farkli bakis açilarina iliskin olarak paradoksal ifadeye verilen yanit da farklilik arz etmektedir. O nedenle paradoks, çözülemez bir sorun ve çatiski olarak karsimizda durmaktadir. Iste bu çözümsüzlügün fark edilmesi, esasinda düsüncenin baslangiç noktasinin fark edilmesidir. Zira sorunun çözümünden çok çözüm yolunu aramak, farkli bakis açilari gelistirmek, felsefi gaye olarak yolun sonunda degil yolda olmak, tam da paradoksun temel pratigidir ve bu sekliyle paradoks, zihinsel bir dinamiktir. Bu sebeple çalismamizin amaci, paradoksun ne oldugu, bir felsefi düsünceye katkisi ve bir mantik problemi olarak akli nasil bir çikmaza sürükledigi üzerinde durmaktir.
Bir Mantik Problemi Olarak Paradoks
Keywords: Logic; Mantik